Uso do Senso Comum na detecção de diferenças culturais no contexto do Projeto OpenMind CommonSense no Brasil - Tsutsumi, Marie (Universidade Federal de São Carlos, 2006)
Knowing what is specific about each culture would be helpful to perform cross cultural communication, because different cultures have different notions of how to begin and develop conversations. Due theses difficulties in differences in cultural norms, we are working to provide to computers this knowledge, since computer environment can allow communication across distance and across cultures. In order to provide to computers cross cultural knowledge, we have collected large knowledge bases representing Common Sense knowledge because we believe that Common Sense knowledge can give some guidelines about different cultures. In our research, we have used bases containing sentences describing common sense knowledge of people and everyday activities, beliefs and values collected from volunteer Web contributors. Furthermore, we describe experiences with these knowledge bases, and we are proposing software which automatically searches for cultural differences related to eating habits, alerting the user to potential differences among cultures. In this way, we hope that our work will contribute to software that takes better account of such differences, and fosters inter-cultural collaboration
Keywords: Interação homem-máquina; Senso comum; OMCS (Open Mind Common Sense); Rede semântica; Diferenças culturais; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO